Control of Helicotylenchus multicinctus and Meloidogyne javanica in established plantain and nematode survival as influenced by rainfall: Combate de helicotylenchus multicinctus y meloidogyne javanica en platano y el efecto de la lluvia sobre la supervivencia de nematodos - Caveness, F.E.; Badra, T. (1980)
Soil treatment with oxamyl and carbofuran at 3 g followed by 1.2 g a.i./plant after 4 months reduced damage caused by Helicotylenchus multicinctus and Meloidogyne javanica to established plantain (Musa AAB). Treatment appreciably reduced nematode populations and significantly increased vigor and yield of plantain. Oxamyl gave the best response followed by carbofuran increasing yields by 98 and 61% respectively. One liquid formulation of oxamyl applied to foliage gave less nematode control and less yield than the granular formulation. In nontreated soils both H. multicinctus and M. javanica juveniles increased or decreased with rainfall. Population densities of both pathogens were significantly correlated with average and/or total rainfall but not correlated with number of rain days. Drought conditions adversely affected M. javanica juveniles populations more than populations of H. multicinctus.